Disorders of Motor, Somatic and Cognitive Development in Children with Neurodysfunctions - Guzik, Agnieszka; Perenc, Lidia; Drużbicki, Mariusz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains the latest findings in a number of research areas, including the effects of dog-assisted therapy on the psychomotor development of children with intellectual disability; the use of weighted blankets and sleep quality in children with autism spectrum disorders; cognitive assessment and rehabilitation for pediatric-onset multiple sclerosis; the use of gait indexes in detecting gait changes in children with spastic hemiplegic cerebral palsy; as well as the effect of ankle joint mobilization, functional progressive resistance exercise, and action observation training on range of motion, gait, spasticity, gross motor function, and balance in children with spastic cerebral palsy. The book is intended for people who work with children and adolescents with neurodysfunctions on a daily basis. It will certainly be useful to physiotherapists, medical doctors, psychologists, and all members of interdisciplinary therapeutic teams. The book can also be recommended to all individuals interested in neurorehabilitation, including parents or guardians of children and adolescents with neurodysfunctions.